Mechanical Characterization of Stir Cast Al 6063 TiO2-Cu Reinforced Hybrid Metal Matrix Composites. (2018) - Lokesh, N.; Manoj, B.; Srikanth, K.; kumar, P.Varun; Ramanayya, P.K.V.; Rao, M.Venkateswara
Abstract: Aluminium based metal matrix composites find varied applications in aerospace, defence, automobile, sports equipment and electronics due to their favourable properties viz. light weight, high strength and coefficient of thermal expansion. Al 6063 is a low strength castable alloy with moderate hardness and strength and finds application in truck wheels and rail road cars. The addition of refractory reinforcement generally improves the hardness, tensile strength and high temperature properties of the material. The present investigation focuses on characterization of metal matrix composites based on Al6063 matrix reinforced with different percentages of Cu and TiO2 particles. Accordingly Al 6063 -TiO2 -Cu composite of 5, 10 &15 wt% Cu as reinforcement are manufactured using conventional stir casting technique. Specimens are prepared as per the ASTM standards and microstructure investigation, tensile, impact and hardness measurements have been correlated with the percentage of Cu particles.